THE CAST IRON INDUSTRY OF PERIGORD (FRANCE) AND A FIREPLACE STOVE IN THE «PROTECTION SYSTEM» OF AN EARLY MODERN HOUSE (LATE 15TH – FIRST HALF OF THE 16TH CENTURY) - BATENKO, Taras (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Аbstract. The article is dedicated to the study of the iron industry in the Périgord region of France in the late 15th to the first half of the 16th century, with a focus on the production of firebacks and their role in the home protection system during the Early Modern period. The research includes an analysis of the technological aspects of iron production in Europe and Périgord, specifically from the extraction of raw materials to the casting and finishing of the final products. Special attention is paid to the study of the fireback as an integral part of the home's interior at that time, serving not only as a source of heat but also playing an important role in protecting the home from fire and other external threats. The work examines the social and economic conditions that contributed to the development of the iron industry in France, including the impact of scientific discoveries and technical innovations, which led to increased quality and productivity in production. The cultural context of fireback use is also analyzed: its symbolic meaning, decorative elements, and aesthetic preferences, which reflected the social status and worldview of the owners. The study shows how the iron industry of Périgord fit into the broader European context of the time, reflecting both general trends and local features of metallurgical development. The article contributes to the understanding of the complex processes that influenced the development of the iron industry in Early Modern Europe and highlights the importance of the fireback as part of the «protection system» of the home, combining functional, cultural, and aesthetic aspects. Based on a wide range of sources, including archaeological finds, graphic materials, and written testimonies, the work provides a multifaceted view of the development of this important sector of the era’s material culture.